Evaluating the effectiveness of active labour market policies in unemployment reduction- a theoretical approach- - Mohamed Kadri; Chourouk Haddouche (Dirassat Journal Economic Issue, 2019)
A major labour market challenge is to avoid an increase in unemployment rates. Active labour market policies may play an important role in this respect. This paper provides a theorical framwork about unemploymet generally as well as new perspective by classifying active labor market programs (ALMPs) depending on their objectives, relevance and cost-effectiveness to reduce unemployment. It distinguishes ALMPs providing incentives for retaining employment, incentives for creating employment, incentives for seeking and keeping a job, incentives for human capital enhancement and improved labor market matching. The paper concludes by providing a empirical evidenes and systematic overview of how, and to what extent specific ALMPs are effective in labour market effect.